Social Entrepreneurship as an Innovation of Coastal Village Government in Maritime-Oriented Economic Development in Riau Islands - Nur Ilmiah Rivai; Muhammad Alfa Sikar (International Conference On Association Of Indonesian Entrepreneurship Study Programs, 2024)
Social Entrepreneurship as an Innovation of Coastal Village Government in Maritime-Oriented Economic Development in the Riau Islands. Social entrepreneurs are individuals or groups who create and implement innovative solutions to social, environmental, and economic problems using entrepreneurial principles. Through Village Law No. 6 of 2014 which mandates the importance of empowering village communities. The Riau Islands, with their strategic location on international trade routes and rich marine resources, have great potential in the development of a maritime-oriented economy. This research will focus on an in-depth analysis of innovations related to social entrepreneurship and community empowerment in the context of improving the economy of coastal villages. The main purpose of this study is to present an analysis of village government innovations in terms of social entrepreneurship. This research method will involve collecting data from various sources of information, including scientific journal databases such as Web of Science, Scopus, and Google Scholar. The data collected will include related publications. This analysis will provide an in-depth understanding of the evolution of knowledge in social entrepreneurship and community empowerment as well as the relationships between stakeholders and identified research trends. The results of research show that coastal village governments on the island of Riau can play a role as social entrepreneurs through various innovations that focus on maritime-oriented economic development. With the right approach, village governments can improve community welfare, protect the marine environment, and promote sustainable and inclusive economic growth. Conclusion These programs can create new jobs and provide sustainable economic opportunities for local residents. Coastal villages in Riau Islands can reduce dependence on the traditional fisheries sector by developing various alternative sources of income. This directly improves the quality of life and socio-economic welfare of coastal communities.